Does Model of Company's added value for Strategy Increasing Stock Prices: Study in Indonesia - Sriyono Sriyono; Yulva Maulit Diana (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2022)
The emergence of the phenomenon of Efficient Market Hypothesis and Theory Overreaction Hypothesis makes it difficult for investors to understand the rise in stock prices. Therefore, additional information is needed on what variables cause changes in stock prices. Research on stock prices has been done by many researchers before, however there is no research that examines by model of value added through panel data model estimation approach. We consider three value-added models that encompass most commonly estimated specifications. The purpose of the study was to find out if the value-added model was capable of increasing stock prices. The population used in this study is a construction company listed on the Indonesian stock exchange. The sampling technique used is purposive sampling, and the number of samples used is 60. The analytical method used is multiple linear regression analysis. The conclusion obtained from this study is that Economic Value Added has a significant negative effect on stock prices. Market Value Added, and Financial Value Added has a significant positive impact on stock prices. The contribution of this research is very large for investors, because the results of this study can be used as a guideline for investors to understand the increase in stock prices.